Pengaruh Pemberian Mulsa Tandan Kosong Kelapa Sawit terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) di Main Nursery - Arifin Yonni Gultom; Sampoerno Sampoerno; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of research to know about the effect of mulching TKKS and get the best dose to the growth of palm oil (Elaeis guineensis Jacq.) seedlings. This research have done in the Garden of Agriculture Faculty, Riau University, Jl. Bina Widya KM 12,5 Simpang Baru, Tampan, Pekanbaru for about four months from Januari until Mei 2016 with using completely randomized design (CRD) Non Faktorial. As for each treatment mulching TKKS (M) is, M0 = Mulching TKKS dose 0 g/plant, M1 = Mulching TKKS dose 15 g/plant, M2 = Mulching TKKS 20 g/plant, M3 = Mulching TKKS 25 g/plant and M4 = 30 g/plant. The parameter which to be subject are seedling height increment, number of leaf increment, leaf area, diameter hump increment, seedling root volume, seedling dry weight, and ratio crown and root. By statistic of analyse data with using DNRMT and to be continue with different experience on level 5%. The result of experience shows that mulching TKKS on palm oil seedlings effect to seedling height increment, number of leaf increment, and seedling dry weight, except leaf area, diameter hump increment, seedling root volume and ratio crown and root. Keywords: Mulching TKKS, Palm Oil